2019
DOI: 10.1093/cercor/bhz010
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Dynamics of Familiar Face Recognition

Abstract: In real-life situations, the appearance of a person's face can vary substantially across different encounters, making face recognition a challenging task for the visual system. Recent fMRI decoding studies have suggested that face recognition is supported by identity representations located in regions of the occipito-temporal cortex. Here, we used EEG to elucidate the temporal emergence of these representations. Human participants (both sexes) viewed a set of highly variable face images of four highly familiar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(82 citation statements)
references
References 78 publications
6
72
4
Order By: Relevance
“…Coding of identities is usually found later. Although earliest results are found from ~100 ms onwards (Ambrus, Kaiser, Cichy, & Kovács, 2019;Vida, Nestor, Plaut, & Behrmann, 2017), higher-level identity representations surpassing low-level visual information (Vida et al, 2017), as well as sensitivity to familiar faces (Schweinberger & Neumann, 2016), are found later, at around 250 ms, and differentiation of same sex identities only after 400 ms (Ambrus et al, 2019).…”
Section: Introductionmentioning
confidence: 90%
“…Coding of identities is usually found later. Although earliest results are found from ~100 ms onwards (Ambrus, Kaiser, Cichy, & Kovács, 2019;Vida, Nestor, Plaut, & Behrmann, 2017), higher-level identity representations surpassing low-level visual information (Vida et al, 2017), as well as sensitivity to familiar faces (Schweinberger & Neumann, 2016), are found later, at around 250 ms, and differentiation of same sex identities only after 400 ms (Ambrus et al, 2019).…”
Section: Introductionmentioning
confidence: 90%
“…Or do they partly reflect idiosyncratic preferences, that is an individual person's unique aesthetic preference for particular faces? To resolve this question, we performed an analysis where we modelled neural RDMs as a function of individual yes/no responses and attractiveness ratings, while controlling for the database ratings using partial correlation analysis [43][44][45] (Figure 2c). We found that individual attractiveness judgments still significantly predicted cortical representations, both when considering yes/no responses (from the 150-200ms time bin; peaking at 600-650ms, peak t [22]=3.87, p<0.001, pcorr=0.002) and when considering attractiveness ratings (from the 150-200ms time bin; peaking at 500-550ms, peak t [22]=3.90, p<0.001, pcorr=0.012).…”
Section: Early Representations Of Facial Attractiveness Reflect Indivmentioning
confidence: 99%
“…To establish correspondences between the neural RDM and a specific predictor RDM while controlling for other RDMs (see below), we used partial correlations [43][44][45]. All correlations were Fisher-transformed before entering them into statistical analyses.…”
Section: Tracking Neural Representations Of Facial Attractivenessmentioning
confidence: 99%
“…Moreover, in a crucial departure from previous efforts to compare the informational requirements of different types of face recognition across distinct task contexts and face presentations, the current thresholds pertain to categorisation functions elicited in parallel by the same face encounters. This notion of concurrence has gained recent traction in the face processing literature, with a number of recent studies using multivariate methods to probe the overlapping time-courses of various types of face categorisation reflected within the same neural response (i.e., decoding "which information is available when", (12)(13)(14)(15)). Here we took a very different approach, capturing differential responses to faces among objects regardless of exact timing (e.g., early/fast vs. late/slow).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, a new wave of face research has emerged aimed at elucidating how the brain extracts information along different face dimensions concurrently (12)(13)(14)(15). In contrast to second-order comparisons of face functions (i.e., contrasts across different tasks/face encounters), this approach investigates the different levels of categorisation reflected in the exact same neural response elicited by a given face encounter, often by applying multivariate pattern analysis (MVPA) techniques to high temporal resolution electro/magneto-encephalographic data (EEG, MEG) (16).…”
Section: Main Textmentioning
confidence: 99%